Penghargaan (Reward) dan Motivasi Kerja terhadap Kinerja Pegawai Pada Badan Standardisasi Instrumen Pertanian Sulawesi Selatan - Angga Teguh Pamuji; H. Saharuddin; Hasiah Hasiah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The Effect of Reward and Work Motivation on Employee Performance at the South Sulawesi Agricultural Instrument Standardization Agency. Thesis Management Study Program of the Indonesian Institute of Education Management (STIM-LPI) Makassar which is supervised by Drs. H. Andi, Saharuddin, MM. and Hasiah, S. E., M.M.This study aims to determine the effect of rewards (Reward) and Work Motivation on Employee performance. The object of this research is the South Sulawesi Agricultural Instrument Standardization Agency. The type of research used is quantitative research by distributing questionnaires via google from. Sampling using saturated sample technique. The results of this study indicate that the partial test Award (Reward) has a significant effect of 0.000 or is below 0.05 while Work Motivation also has a strong influence on Employee Performance but when compared between Award and Work Motivation.